2014
DOI: 10.1186/1475-2859-13-61
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale metabolic network reconstruction and in silico flux analysis of the thermophilic bacterium Thermus thermophilus HB27

Abstract: BackgroundThermus thermophilus, an extremely thermophilic bacterium, has been widely recognized as a model organism for studying how microbes can survive and adapt under high temperature environment. However, the thermotolerant mechanisms and cellular metabolism still remains mostly unravelled. Thus, it is highly required to consider systems biological approaches where T. thermophilus metabolic network model can be employed together with high throughput experimental data for elucidating its physiological chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…However, a communality is that all three strains relied heavily on glycolysis and the TCA cycle. Studies on Thermus thermophilus, possibly the most well-studied thermophile, revealed alternative pathways of amino acids synthesis, with lysine being synthesized by alpha-aminoadipate pathway instead of diaminopimelate pathway (Kosuge and Hoshino 1998) and homocysteine produced from an alternative precursor, O-acetyl-L-homoserine (Lee et al 2014) . T. thermophilus is also known to produce a variety of polyamines, the most common ones, spermidine and spermine, are synthesised using a distinct pathway from L-arginine via aminopropyl agmatine (Oshima 2007) .…”
Section: Introductionmentioning
confidence: 99%
“…However, a communality is that all three strains relied heavily on glycolysis and the TCA cycle. Studies on Thermus thermophilus, possibly the most well-studied thermophile, revealed alternative pathways of amino acids synthesis, with lysine being synthesized by alpha-aminoadipate pathway instead of diaminopimelate pathway (Kosuge and Hoshino 1998) and homocysteine produced from an alternative precursor, O-acetyl-L-homoserine (Lee et al 2014) . T. thermophilus is also known to produce a variety of polyamines, the most common ones, spermidine and spermine, are synthesised using a distinct pathway from L-arginine via aminopropyl agmatine (Oshima 2007) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to construct the lumped biomass equation the composition of biomass of T. thermophilus LC113 grown at 81 °C was measured using the methods described in (Long and Antoniewicz, 2014). Figure 3 compares the measured biomass composition for T. thermophilus LC113 and the biomass composition previously reported for T. thermophilus HB27 (Lee et al, 2014). Overall, we measured a higher protein content for T. thermophilus LC113 (68% of dry weight) compared to T. thermophilus HB27 (50 wt%), and a lower RNA content (10 wt%) compared to 21 wt% for T. thermophilus HB27 (note that the value of 21 wt% was not measured directly, but was assumed the same as for E. coli ).…”
Section: Resultsmentioning
confidence: 83%
“…These results suggest that different T. thermophilus strains grown at different temperatures may have a significantly different biomass composition, i.e. biomass composition of T. thermophilus HB27 was characterized at 70 °C (Lee et al, 2014). It is therefore important to measure biomass composition under relevant experimental conditions to ensure that the biomass reaction used for 13 C-MFA calculations is representative of the organism studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations